Effect of feed supplementation on chemical composition of meat of three genotypes of scavenging ducklings in coastal areas of Bangladesh (Bangladesh Journal of Animal Science, 2014)
The present study was conducted to evaluate the chemical composition of three genotypes of scavenging ducklings (Muscovy, Pekin and Desi White) in coastal areas of Bangladesh. Three ducks from each genotype were slaughtered at 6, 10 and 14th week of age. The results indicated that dry matter yield was highest in Muscovy (40.91 and 44.40) followed by Pekin (39.30 and 44.31) and Desi White (35.67 and 41.82) for control and supplemental group, respectively at 14th week of age. The concentration of crude protein was highest in Muscovy (18.76 and 19.90), intermediate in Pekin (18.40 and 19.66) and the lowest in Desi White (17.20 and 19.14) for two feeding regimes at 14th week of age. The ether extract content varied from 17.21 to 23.16. Genotype and feed showed significant effect (p0.05) effect on ash content at 14th week of age. Genotypes and feed showed significant effect (p0.05) on DM and moisture content of duck meat.DOI: http://dx.doi.org/10.3329/bjas.v43i1.19381 Bang. J. Anim. Sci. 2014. 43 (1): 25-29